Suppression of ERα Activity by COUP-TFII Is Essential for Successful Implantation and Decidualization - Lee, Dong-Kee (The Endocrine Society, 2010)
Synchrony between embryo competency and uterine receptivity is essential for successful implantation. Mice with ablation of chicken ovalbumin upstream promoter-transcription factor II (COUP-TFII) in the uterus (PR(Cre/+);COUP-TFII(flox/flox)) exhibit implantation defects and increased estrogen receptor (ER)α activity in the luminal epithelium, suggesting high ERα activity may disrupt the window of uterine receptivity. To determine whether increased ERα activity in the PR(Cre/+);COUP-TFII(flox/flox) uterus is the cause of defective implantation, we assessed whether inhibition of ERα activity could rescue the PR(Cre/+);COUP-TFII(flox/flox) uterine implantation defect. ICI 182,780 (ICI), a pure ERα antagonist, was administered to PR(Cre/+);COUP-TFII(flox/flox) mutant and COUP-TFII(flox/flox) control mice during the receptive period, and the number of implantation sites was examined. COUP-TFII(flox/flox) control mice treated with oil or ICI showed the normal number of implantation sites. As expected, no implantation sites were observed in PR(Cre/+);COUP-TFII(flox/flox) mutant mice treated with oil, consistent with previous observations. In contrast, implantation sites were greatly increased in ICI-treated PR(Cre/+);COUP-TFII(flox/flox) mutant mice, albeit at a reduced number in comparison with the control mice. ICI treatment was also able to restore the expression of Wnt4 and bone morphogenetic protein 2, important for endometrial decidualization in the PR(Cre/+);COUP-TFII(flox/flox) mutant mice. To confirm that the rescue of embryo attachment and decidualization is a consequence of a reduced ERα activity upon ICI treatment, we showed a reduction of the expression of ERα target genes in PR(Cre/+);COUP-TFII(flox/flox) mutant mice. Because COUP-TFII was also shown in our laboratory to be important for placentation during pregnancy, we asked whether ICI treatment could also rescue the placentation defect to allow full-term pregnancy in these mice. We found that whereas mice were born in COUP-TFII(flox/flox) control mice given ICI, no pups were born in the PR(Cre/+);COUP-TFII(flox/flox) mutant mice, suggesting that the increased ERα activity is not the reason for placentation defects. These results demonstrate that during the periimplantation period, COUP-TFII regulates embryo attachment and decidualization through controlling ERα activity. However, COUP-TFII expression is still required in the postimplantation period to facilitate placentation.